133 Multiple sclerosis and the risk of infection: a consensus guideline. Issue 9 (12th August 2022) - Cauchi, Marija; Willis, Mark; Backx, Matthijs; Brownlee, Wallace; Ford, Helen; Gran, Bruno; Jolles, Stephen; Price, Sian; Tallantyre, Emma
Abstract : Multiple sclerosis (MS) is an inflammatory condition affecting the central nervous system. Infection is a major consideration in the MS population due to its relevance to several stages of the disease process: (i) it has been suggested that infective processes may be 'triggering' or aetiological factors for MS, (ii) concurrent infection is known to exacerbate symptoms in MS, (iii) people with MS are at higher risk of infection when compared to the general population, and this risk is exaggerated in those receiving disease modifying therapies (DMTs). This guidance document was developed by specialists in the field of MS, Immunology, Infectious Disease and Pharmacy. A modified Delphi approach was used to develop clinically relevant, evidence-based consensus guidelines to help physicians navigate the complex interaction between DMTs and infectious diseases. We focus on specific risks predisposing people with MS to infection and how to manage these risks. We also provide recommendations on how to screen for, prevent, and manage infection in this population, in particular tuberculosis, progressive multifocal leukoencephalopathy, hepatitis B, human papillomavirus, herpetic and other opportunistic infections. We also discuss vaccination and the COVID-19 pandemic in people on DMTs.